The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1086/315010
|View full text |Cite
|
Sign up to set email alerts
|

Lower Human Immunodeficiency Virus (HIV) Type 2 Viral Load Reflects the Difference in Pathogenicity of HIV‐1 and HIV‐2

Abstract: Human immunodeficiency virus type 2 (HIV-2) is less pathogenic than HIV type 1 (HIV-1), but the mechanisms underlying this difference have not been defined. We developed an internally controlled quantitative reverse transcriptase-polymerase chain reaction to measure HIV-2 viral load and determined levels of plasma virus in a cohort of registered commercial sex workers in Dakar, Senegal. The assay has a lower limit of detection of 100 copies/mL and is linear over 4 logs. HIV-2 viral RNA was detectable in 56% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
131
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(147 citation statements)
references
References 36 publications
(18 reference statements)
13
131
0
Order By: Relevance
“…Most HIV-2 + individuals are long-term nonprogressors (LTNP) with low or undetectable viral loads [1,2]. Therefore, HIV-2 infection has the features of an 'attenuated' HIV-1 infection, but evidence for a true attenuated phenotype is lacking [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most HIV-2 + individuals are long-term nonprogressors (LTNP) with low or undetectable viral loads [1,2]. Therefore, HIV-2 infection has the features of an 'attenuated' HIV-1 infection, but evidence for a true attenuated phenotype is lacking [3].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas HIV-1 group M subtypes (A-D, F, H, J, and K) are spread globally, HIV-2 subtypes are mainly restricted to West Africa and can be categorized as epidemic subtypes (A and B) and nonepidemic subtypes (C-G) (4)(5)(6)(7). Biological reasons have been invoked to explain the difference in global epidemiology between HIV-1 and HIV-2, such as lower HIV-2 viral loads that correlate with a lower transmissibility (8)(9)(10). However, attempts to compare the history of the epidemics at their respective geographic origins are still lacking.…”
mentioning
confidence: 99%
“…Again, it might mean that this particular VBD was positive for HIV-2 which is less virulent and have lower progression to AIDS compared to HIV-1 [12]. Studies have showed the inverse relationships between HIV viral loads and CD4+ T-lymphocytes [45,46]. DOR adopted in this study validated the reliability of the results of rapid antibody techniques (based on serial algorithm II).…”
Section: Discussionmentioning
confidence: 59%